The changing size distribution of US trade unions and its description by Pareto's distribution - John H. Pencavel (Institute for the Study of Labor (IZA), 2013)
The size distribution of trade unions in the United States and changes in this distribution are documented. Because the most profound changes are taking place among very large unions, these are subject to special analysis by invoking Pareto's distribution. This represents a new application of this distribution. Extensions to trade union wealth and to Britain are broached. The role of the public sector in these changes receives particular attention. A simple model helps account both for the logarithmic distribution of union membership and for the contrasting experiences of public and private sector unions since the 1970s.
Keywords: J51; 330; trade union membership; public-sector unions; Pareto's distribution